Soil phosphorus form affects the advantages that arbuscular mycorrhizal fungi confer on the invasive plant species, Solidago canadensis, over its congener - Chen, Li; Wang, Mengqi; Shi, Yu; Ma, Pinpin; Xiao, Yali; Yu, Hongwei; Ding, Jianqing (Frontiers in Microbiology, 2023)
Interactions between plants and arbuscular mycorrhizal fungi (AMF) are strongly affected by soil phosphorus (P) availability. However, how P forms impact rhizosphere AMF diversity, community composition, and the co-occurrence network associated with native and invasive plants, and whether these changes in turn influence the invasiveness of alien species remain unclear. In this work, we performed a greenhouse experiment with the invasive species Solidago canadensis and its native congener S. decurrens to investigate how different forms of P altered the AMF community and evaluate how these changes were linked with the growth advantage of S. canadensis relative to S. decurrens. Plants were subjected to five different P treatments: no P addition (control), simple inorganic P (sodium dihydrogen phosphate, NaP), complex inorganic P (hydroxyapatite, CaP), simple organic P (adenosine monophosphate, AMP) and complex organic P (myo-inositol hexakisphosphate, PA). Overall, invasive S. canadensis grew larger than native S. decurrens across all P treatments, and this growth advantage was strengthened when these species were grown in CaP and AMP treatments. The two Solidago species harbored divergent AMF communities, and soil P treatments significantly shifted AMF community composition. In particular, the differences in AMF diversity, community composition, topological features and keystone taxa of the co-occurrence networks between S. canadensis and S. decurrens were amplified when the dominant form of soil P was altered. Despite significant correlations between AMF alpha diversity, community structure, co-occurrence network composition and plant performance, we found that alpha diversity and keystone taxa of the AMF co-occurrence networks were the primary factors influencing plant growth and the growth advantage of invasive S. canadensis between soil P treatments. These results suggest that AMF could confer invasive plants with greater advantages over native congeners, depending on the forms of P in the soil, and emphasize the important roles of multiple AMF traits in plant invasion.